A METAPRAGMATIC ANALYSIS: A STUDY OF PRAGMATIC FAILURE FOUND IN INDONESIAN EFL STUDENTS - Merawati Hutauruk; Dian Puspita (Linguistics and Literature Students' Journal, 2020)
This research aimed to investigate the possibilities of pragmatic failure done by Indonesian EFL students through their translation. This study employed theories by Thomas (1983) and Muir et al (2011) to answer the research question coming along with the problem concerned. As mentioned by Natrio (2018) that Indonesian EFL students lack pragmatic competence because they don’t recognize the intention of one language transferring is inappropriate. This research used a descriptive qualitative method in collecting the data. The data were coming from students‟ performance in translating short dialogue texts which contained idioms in them. The instrument given was two-way translation, English-Indonesian, and vice versa. As the result, this study found that the respondents experienced pragmatic failure in their performance which happened in several types, namely pragma-linguistic failure and socio-pragmatic failure, both of which were found in all types of texts given. It was also found that the failure that happened in English-Indonesian text was higher in number compared to the other type of text in which in all the data found, the failure in English –Indonesian text translation is 161 while in Indonesian-English text translation is 139. On the other hand, this study also revealed that the factors of the students‟ pragmatic failure that happened in their translation performance were coming from both the pragmatic transfer which influenced by either their native, source language or their understanding and lack of linguistic proficiency.